Combined metformin and simvastatin therapy inhibits SREBP2 maturation and alters energy metabolism in glioma - Xiaolong Qiao; Zixuan Wang; Yinan Chen; Nan Peng; Hongwei Zhang; Chaoshi Niu; Chuandong Cheng (Cell Death and Disease)
Abstract This study aims to explore the inhibitory effects of combined metformin and simvastatin therapy on the malignant progression of glioma. The research specifically examines how the maturation of SREBP2 as a transcription factor affects the expression of GLUT1 and GLUT6 in glioma cells. Additionally, it investigates the impact of this combination therapy on the biological functions and energy metabolism of glioma cells. To assess the functions of GLUT1/6, sh-GLUT1/6 plasmids were employed. The study determined the half-maximal inhibitory concentrations (IC50) of metformin and simvastatin using the CCK-8 assay. Subsequently, the effects of these drugs on glioma metabolism, proliferation, and apoptosis were explored in vitro and in vivo, using drug concentrations significantly lower than their respective IC50 values. The impact of drug treatment on GLUT1/6 and SREBP2 expression levels was also evaluated. The study elucidated the significant impact of GLUT1/6 on glioma cell functions, resulting in decreased glucose uptake. Moreover, it unveiled the regulatory role of SREBP2 in GLUT1 and GLUT6 transcription, alongside revealing differential expression of SREBP2 precursor and mature forms within gliomas. Following combined drug therapy, GLUT1/6 expression decreased, while the precursor form of SREBP2 increased, and mature SREBP2 reduced. This dual-drug treatment effectively modulated glioma cell energy metabolism. Subsequent in vivo experiments affirmed the augmented anti-tumor efficacy of combined drug therapy. Specifically, the synergistic action of metformin and simvastatin reshaped glioma metabolism, curbed malignant proliferation, promoted apoptosis, and demonstrated superior anti-tumor effects both in vitro and in vivo compared to individual administration of metformin or simvastatin. Importantly, the combination therapy achieved these effects at lower doses, rendering it a safer treatment option.